(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Water tests were gathered from stream Jhelum at various areas over a stretch of 20 km from Lasjan to Parimpora in the Srinagar city of Jammu & Kashmir (UT), India. These examples were dissected for 14 water quality factors - physical and chemical boundaries. The information related physico-chemical boundaries of water of waterway Jehlum acquired during the review have been referenced underneath in Table 1. During the course of study, it was additionally seen that the convergence of a portion of these boundaries was not in agreement to as far as possible suggested by World Health Organization. This could have a unmistakable effect on life. The outcomes acquired during the review show that the topographical area and season straightforwardly affect the different physico-substance boundaries of stream Jehlum. It is accepted that this study will be useful in figuring out control technique in not so distant future.